Ion exchanger and preparation method and application thereof
Na5n[NaP4V10O34]n·xH2O ion exchanger prepared by hydrothermal reaction solves the problems of low adsorption capacity, slow adsorption rate, poor acid-base resistance and radiation resistance when adsorbing Cs+ and Sr2+ ions. , achieving efficient and stable adsorption effect and excellent acid and alkali resistance and radiation resistance.
Patent Information
- Application Number
- CN202510050292.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-13
AI Technical Summary
When adsorbing Cs+ and Sr2+ ions, existing ion exchangers have problems such as low adsorption capacity, slow adsorption rate, poor acid and alkali resistance and radiation resistance, which limits their application in the field of radioactive waste disposal.
An ion exchanger with a structure of Na5n[NaP4V10O34]n·xH2O is prepared by dissolving V2O5, Na2HPO4·10H2O and alkaline substances in distilled water, adding acidic substances to adjust the pH value, and conducting hydrothermal reactions.
The ion exchanger has a high adsorption rate and a high adsorption amount, can maintain stability in an environment with pH=3-12, the removal rate during adsorption equilibrium reaches more than 97%, and has excellent acid and base and radiation tolerance.
Smart Images

Figure CN119456056A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nuclear wastewater treatment, and in particular to an ion exchanger and a preparation method and application thereof. Background Art
[0002] Nuclear power is a high-tech industry that integrates technology and capital. It is of great significance to the construction of a modern energy system, the protection of the ecological environment, the response to climate change, and the promotion of scientific and technological progress. How to properly dispose of radioactive waste and improve the ability to respond to nuclear incidents is the primary task of implementing nuclear safety and radioactive pollution prevention and control. 137 Cs and 90 Sr is a high-energy fission product released during the operation of a nuclear reactor, mainly Cs + , Sr 2+ In the form of positive ions, it poses a potential hazard to human health. Therefore, if radionuclides can be captured promptly and quickly in a nuclear incident and their spread can be blocked, the effectiveness of nuclear pollution control will be greatly improved, thereby ensuring nuclear safety, the environment and public health.
[0003] In addition, after separation and purification 137 Cs, 90 Radioactive nuclides such as Sr can still be used for nuclear power generation and radioactive nuclide radiation sources to achieve their comprehensive utilization. 137 Cs and 90 Sr is used in scientific research, medical treatment, liquid level and density measurement, electrostatic dust removal, food disinfection, and preparation of special materials (phosphors).
[0004] At present, Cs in water + , Sr 2+ The extraction methods of Cs include precipitation, extraction, membrane filtration, biological treatment, adsorption and ion exchange. Among these methods, ion exchange has attracted people's attention due to its high recovery rate, good purification effect, simple operation and no secondary pollution. Among them, inorganic materials represented by clay, zeolite, ferrocyanide and molecular sieve are the most effective in the extraction of Cs. + , Sr 2+ However, these materials still have problems such as low adsorption capacity, slow adsorption rate and poor acid and alkali resistance, which limit their application in the field of radioactive waste disposal.
[0005] Based on this, there is an urgent need to develop high-capacity ion exchange materials that are resistant to acid, alkali and radiation to achieve Cs + , Sr 2+ Efficient removal and purification. Summary of the invention
[0006] In order to solve the problems of low adsorption capacity, slow adsorption rate, poor acid and alkali resistance and radiation resistance of ion exchangers in the prior art, one of the objects of the present invention is to provide a method for preparing the ion exchanger.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing an ion exchanger is disclosed. The preparation of the ion exchanger comprises the following steps: dissolving V2O5 (vanadium pentoxide), Na2HPO4·10H2O (disodium hydrogen phosphate decahydrate) and an alkaline substance in distilled water to form a reaction solution, adding an acidic substance to the reaction solution to adjust the reaction solution to be weakly acidic, and then performing a hydrothermal reaction to obtain the ion exchanger.
[0008] The beneficial effects of the present invention are as follows: the preparation process of the ion exchanger of the present invention does not involve the use of precious metals and has low cost; in the synthesis process, an alkaline substance is first used to promote the hydrolysis of vanadium pentoxide to form soluble vanadate; then an acidic substance is used to promote the acidification of the reaction system, thereby accelerating the aggregation of vanadate anions into clusters, which is beneficial to improving the yield of the ion exchanger, and there is no by-product in the entire reaction process.
[0009] On the basis of the above technical solution, the present invention can also be improved as follows: Further, the molar ratio of V2O5 and Na2HPO4·10H2O is 1:0.5-0.8; The pH value of the reaction solution after adjustment by the acidic substance is 3.8-4; The hydrothermal reaction conditions are: temperature 180-200°C, time 72-96h; The alkaline substance is diethylamine or pyridine; the acidic substance is acetic acid.
[0010] The beneficial effects of the above technical solution are as follows: In the present invention, the reaction solution is within the acidic range to avoid insufficient acidity of the reaction solution, which may lead to decomposition of vanadium oxygen clusters and hinder the reaction. It also avoids excessive acidity, which may lead to the formation of a black amorphous phase instead of VPO-1. In addition, the acidic substance in the present invention is acetic acid, because when acetic acid is used to adjust the solution to weak acidity, acetic acid plays a buffering role in the reaction process, so that the pH change in the reaction process will not be too large, thereby ensuring the formation of an ion exchanger.
[0011] The second object of the present invention is to provide an ion exchanger prepared by the preparation method of the first object, the general structural formula of the ion exchanger is Na 5n [NaP4V 10 O 34 ] n ·xH2O, where n>0 and x is the number of free water molecules; the ion exchanger is [NaP4V 10 O 34 ]5- Cluster formation, [NaP4V 10 O 34 ] 5- The clusters are connected by oxygen atoms on the phosphate groups and extend infinitely around to form a three-dimensional anion framework, with the remaining sodium ions located within the framework.
[0012] Beneficial effects of the present invention: The ion exchanger of the present invention has a great influence on the + and Sr 2+ The ions have extremely high adsorption rate and adsorption capacity. They can remain stable in the pH range of 3-12 of the solution to be treated. The contact time in column filtration and membrane filtration is only 0.65-8.2s, and the removal rate at adsorption equilibrium can still reach more than 97%.
[0013] Furthermore, [NaP4V 10 O 34 ] 5- The cluster is formed by two V5O7 units and four phosphate groups encapsulating one Na ion.
[0014] The third object of the present invention is to provide an application of an ion exchanger, wherein the application is to directly add the ion exchanger prepared in the first object or the ion exchanger in the second object to a Cs-containing + and / or Sr 2+ In the solution to be treated, Cs + and / or Sr 2+ Adsorption; The pH value of the solution to be treated is 3-12; 1 g of ion exchanger is added to every 50-3000 mL of the solution to be treated; Cs in the solution to be treated + The concentration of ions is 0.1-3000ppm; Sr 2+ The concentration of ions is 0.1-3000ppm.
[0015] Furthermore, the solution to be treated also contains Na + , K + Mg 2+ and Ca 2+ At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm.
[0016] The fourth object of the present invention is to provide an application of an ion exchanger, which is prepared by filling the ion exchanger prepared in the first object or the ion exchanger in the second object into a chromatography column, and allowing the ion exchanger containing Cs + and / or Sr 2+ The solution to be treated flows through, and the Cs + and / or Sr 2+ Adsorption; Cs in the solution to be treated + and Sr 2+ The concentration of ions is 0.5-3000 ppm; Every 1 cm 3 The flow rate of the solution to be treated by ion exchanger is 0.1-5 mL min -1 ; The pH value of the solution to be treated is 3-12.
[0017] Furthermore, the solution to be treated also contains Na + , K + Mg 2+ and Ca 2+ At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm. The fifth object of the present invention is to provide an application of an ion exchanger, which is as follows: first, the ion exchanger prepared in the first object or the ion exchanger in the second object is made into powder and then added into N-methylpyrrolidone dissolved with polyvinylidene fluoride to form a mixture, then the mixture is taken out and evenly scraped on the surface of a water-based PTFE (polytetrafluoroethylene) microporous filter membrane substrate, and naturally dried in the air to obtain a composite microporous filter membrane composed of an ion exchanger and PTFE; by suction filtration, the ion exchanger containing Cs + and / or Sr 2+ The solution to be treated flows through the composite microporous filter membrane, and the Cs + and / or Sr 2+ Adsorption; The mass ratio of the ion exchanger to polyvinylidene fluoride is 5-40:1; The thickness of the water-based PTFE microporous filter substrate is 30-200 µm; The layer thickness of the ion exchanger in the composite microporous membrane is 10-200 µm; Every 1 cm 2The flow rate of the composite microporous membrane to treat the solution is 0.5-2.5 mL min -1 ; Cs in the solution to be treated + and Sr 2+ The concentration of the ions is 0.5-3000 ppm; the pH value of the solution to be treated is 3-12.
[0018] Furthermore, the particle size of the powder made of the ion exchanger is 1-10 μm; The solution to be treated also contains Na + , K + Mg 2+ and Ca 2+ At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm.
[0019] Further preferably, the third, fourth and fifth purposes of adsorbing Cs + and / or Sr 2+ The ion exchanger can be eluted with 0.5-3 M NaCl solution to remove the Cs adsorbed in the ion exchanger. + and / or Sr 2+ , awaken the activity of ion exchangers and realize the reuse of ion exchangers.
[0020] The present invention has the following beneficial effects: 1. The preparation method of the present invention has the characteristics of simple process, high yield, no by-products and good repeatability. In addition, the raw materials of vanadium pentoxide and disodium hydrogen phosphate in the present invention are easy to obtain, which reduces the preparation cost of the ion exchanger.
[0021] 2. The present invention uses a hydrothermal method to react V2O5 with Na2HPO4·10H2O. During the reaction, Na + Ions are introduced into the crystal lattice to obtain an ion exchanger; after testing, it is found that the ion exchanger has excellent acid-base and radiation tolerance. And the ion exchanger in the present invention is [NaP4V 10 O 34 ] 5- Clusters and hydrated Na + Cation composition, of which hydrated Na + Ions can react with Cs + , Sr 2+ Exchange to achieve ion exchange of Cs+ , Sr 2+ The ion exchanger prepared in the present invention has a strong adsorption capacity for Cs under different acidity conditions of the solution to be treated. + , Sr 2+ The mixed ions exhibited excellent adsorption function, with the characteristics of large adsorption capacity, fast kinetic response, high separation coefficient and convenient elution.
[0022] 3. The ion exchanger prepared by the present invention has a larger pore size and is suitable for Cs + and Sr 2+ The ions have good adsorption effect, fast adsorption rate and high adsorption capacity, and can remove more than 98% of 6 ppm Cs in 10 minutes + and Sr 2+ , suitable for emergency treatment of large-scale water bodies containing radioactive ions.
[0023] 4. The ion exchanger prepared by the present invention is in an environment of pH=3-12 and in the presence of Na + , K + , Ca 2+ ,Mg 2+ , Al 3+ , Fe 3 + ,Eu 3+ , UO2 2+ , NO3 - , SO4 2- ,CO3 2- , HCO3 - In the environment of interfering ions such as Cs + and Sr 2+ They all have a high removal rate and can therefore be applied to the treatment and disposal of high-level radioactive nuclear waste liquid at home and abroad.
[0024] 5. When the ion exchanger of the present invention is used, column filtration or membrane filtration can be selected or it can be directly contacted with the solution to be treated. Through testing, it is found that the ion exchanger of the present invention has a significant effect on the Cs in the solution to be treated by continuous flow (column filtration or membrane filtration). + and Sr 2+ The ion removal rate is higher than 97%. Especially when using membrane filtration, the composite microporous filter membrane can remove Cs in a very short contact time. + and Sr 2+ Ions are removed efficiently and can be recycled.
[0025] In addition, the ion exchanger in the present invention adsorbs Cs + and Sr 2+ After ionization, the Cs in the ion exchanger can be removed by high concentration brine. + and Sr 2+Elution was performed to complete the Cs + and Sr 2+ The ion exchanger can be recovered and its activity can be reawakened, which is conducive to its reuse. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The morphology diagram of the ion exchanger (VPO-1) prepared in Example 1 of the present invention, wherein (a) is an appearance morphology diagram of the ion exchanger, and (b) is an enlarged appearance morphology diagram of the ion exchanger; Figure 2 Schematic diagram of the crystal structure of the ion exchanger (VPO-1) prepared in Example 1 of the present invention; wherein (a) is {NaP4V 10 O 34}cluster composition diagram; (b) The figure shows [NaP4V 10 O 34 ] n 5n- (c) The topology of the VPO-1 framework; (d) The topology of the 18 {NaV 10 O 26}Schematic diagram of the nanoscale cavity encapsulated by the cluster; Figure 3 This is an energy dispersive X-ray spectrum of the ion exchanger (VPO-1) prepared in Example 1 of the present invention; Figure 4 This is the thermogravimetric diagram of the ion exchanger (VPO-1) prepared in Example 1 of the present invention; Figure 5 The ion exchanger (VPO-1) prepared in Example 1 of the present invention and its reaction with Cs + , Sr 2+ XRD patterns of saturated exchange products VPO-1Cs and VPO-1Sr; Figure 6 XRD diagram of the ion exchanger (VPO-1) prepared in Example 1 of the present invention before and after irradiation with 150 kGy β or 150 kGy γ rays; Figure 7 The ion exchanger (VPO-1) prepared in Example 1 of the present invention is used for Cs + or Sr 2+ The change of ion removal rate over time, where (a) is the VPO-1 sample for Cs + The removal rate of ions changes with time. (b) The VPO-1 sample is Sr 2+ Graph showing the change in ion removal rate over time; Figure 8 The ion exchanger (VPO-1) prepared in Example 1 of the present invention is used for Cs+ or Sr 2+ Ion isotherm adsorption curve and fitting result diagram, among which (a) is the VPO-1 ion exchanger for Cs + Ion adsorption isotherm curve and fitting results. (b) Figure shows the adsorption of Sr by VPO-1 ion exchanger. 2+ Ion adsorption isotherm curve and fitting result diagram; Fig. 9 The ion exchanger (VPO-1) prepared in Example 1 of the present invention and Cs + Energy dispersive X-ray spectra of the ion exchange product VPO-1Cs; Fig.10 The ion exchanger (VPO-1) prepared in Example 1 of the present invention and Sr 2+ Energy dispersive X-ray spectrum of the saturation exchange product VPO-1Sr; Fig.11 The ion exchanger (VPO-1) prepared in Example 1 of the present invention contains a single Cs + or Sr 2+ The distribution coefficient of ion adsorption varies with the pH value of the solution. (a) shows the distribution coefficient of ion adsorption of VPO-1 in the treated solution containing a single Cs + The distribution coefficient of ion adsorption varies with the pH value of the solution. (b) The figure shows the distribution coefficient of ion adsorption of VPO-1 in the treated solution containing a single Sr 2+ The distribution coefficient of ion adsorption changes with the pH of the solution; Fig.12 The VPO-1 ion exchanger of the present invention is used for single Cs + , Sr 2+ Ion adsorption removal rate changes with the type and concentration of coexisting ions in the solution to be treated, where (a) is the removal rate of Cs by VPO-1 ion exchanger. + The removal rate of ion adsorption varies with the type and concentration of coexisting ions in the solution to be treated. (b) The removal rate of ion adsorption by VPO-1 ion exchanger is Sr 2+ The removal rate of ion adsorption varies with the type and concentration of coexisting ions in the solution to be treated; Fig.13 The VPO-1 ion exchanger of the present invention contains CO3 in the solution to be treated. 2- 、HCO3 - 、NO3 - or SO4 2- When present, single Cs + , Sr 2+ (6 ppm) removal rate by ion adsorption; Fig.14The VPO-1 ion exchanger of the present invention contains Fe 3+ 、Al 3+ 、Eu 3+ or UO2 2+ When present, single Cs + , Sr 2+ (6 ppm) removal rate by ion adsorption; Fig.15 This is a diagram of a chromatography column device filled with a VPO-1 ion exchanger in the present invention; Fig.16 The chromatographic column filled with the VPO-1 ion exchanger of the present invention is used to treat Cs in the solution + , Sr 2+ Ion removal rate versus bed volume trend graph; Fig.17 Cs in the present invention + and Sr 2+ SEM photos and element distribution diagrams of the saturated exchange products VPO-1Cs-Na and VPO-1Sr-Na after elution; Fig.18 Cs + This is the energy dispersive X-ray spectrum of the product VPO-1Cs-Na after elution of the saturated exchange product; Fig.19 Sr 2+ This is the energy dispersive X-ray spectrum of the product VPO-1Sr-Na after elution of the saturated exchange product; Fig. 20 is a SEM image of the cross section of the VPO-1 / PTFE composite microporous filter membrane of the present invention; Fig.21 This is a photograph of the VPO-1 / PTFE composite microporous filter membrane during the test process of the present invention; Fig. 22 The composite microporous filter membrane of VPO-1 / PTFE in the present invention is mixed with Cs + , Sr 2+ Ion removal (2 ppm of each ion) versus treatment solution volume. DETAILED DESCRIPTION
[0027] An ion exchanger, a preparation method and an application thereof in the present application will be described below in conjunction with embodiments.
[0028] However, the present application may be exemplified in many different forms and should not be construed as limited to the specific embodiments set forth herein. Rather, these embodiments are provided so that the present application will be thorough and complete and will fully convey the scope of the present application to those skilled in the art.
[0029] Example 1 A method for preparing an ion exchanger is as follows: 1mmol V2O5 and 0.5mmol Na2HPO4·10H2O were added to a mixed solution formed by 0.2ml diethylamine and 2mL distilled water and stirred to obtain a reaction solution, and then acetic acid solution was added to adjust the pH value of the reaction solution to 4, and finally the solution was transferred to a reactor and reacted at 200°C for 72h. After the reaction, the solution was naturally cooled to room temperature, washed with water and dried naturally to obtain an ion exchanger (VPO-1).
[0030] Furthermore, the yield of the ion exchanger calculated based on P was 87%; wherein, yield=(mass of the obtained ion exchanger sample / molecular weight of the product×4) / (molar number of P)×100%.
[0031] Example 2 A method for preparing an ion exchanger is as follows: 1mmol V2O5 and 0.8mmol Na2HPO4·10H2O were added to a mixed solution formed by 0.2ml diethylamine and 2mL distilled water and stirred to obtain a reaction solution, and then acetic acid solution was added to adjust the pH value of the reaction solution to 3.8, and finally the reaction solution was transferred to a reactor and reacted at 200°C for 72h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed with water and dried naturally to obtain a VPO-2 ion exchanger.
[0032] And, the yield calculated based on P is 83%; wherein, yield=(mass of the obtained VPO-2 ion exchanger sample / molecular weight of the product×4) / (molar number of P)×100%.
[0033] Example 3 A method for preparing an ion exchanger is as follows: 1mmol V2O5 and 0.5mmol Na2HPO4·10H2O were added to a mixed solution formed by 0.2ml diethylamine and 2mL distilled water and stirred to obtain a reaction solution, and then acetic acid solution was added to adjust the pH value of the reaction solution to 4, and finally the reaction solution was transferred to a reactor and reacted at 180°C for 96h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed with water and dried naturally to obtain a VPO-3 ion exchanger.
[0034] And, the yield calculated based on P is 80%; wherein, yield=(mass of the obtained VPO-3 ion exchanger sample / molecular weight of the product×4) / (molar number of P)×100%.
[0035] Example 4 An application of an ion exchanger is as follows: 1. Used to adsorb Cs + The ion exchanger is used as follows: the ion exchanger (VPO-1) prepared in Example 1 is added with Cs + ions in the solution to be treated, and continued stirring at room temperature (20°C) for 60 minutes, and a small amount of the supernatant of the mixture was taken at 0.5, 1, 2, 5, 10, 20, 40, and 60 minutes for testing. + The concentration of ions is 6 ppm, and the ratio of the treated solution to the ion exchanger is: V / m = 1000 mL g -1 , the pH of the solution to be treated is 6.
[0036] 2. Used to adsorb Sr 2+ The ion exchanger is used as follows: the ion exchanger (VPO-1) prepared in Example 1 is added with Sr 2+ ions in the solution to be treated, and continued stirring at room temperature (20°C) for 60 minutes, and a small amount of the supernatant of the mixture was taken at 0.5, 1, 2, 5, 10, 20, 40, and 60 minutes for testing. 2+ The concentration of ions is 6 ppm, and the ratio of the treated solution to the ion exchanger is: V / m = 1000 mL g -1 , the pH of the solution to be treated is 6.
[0037] Example 5 An application of an ion exchanger, specifically: Fig.15 The chromatographic column device diagram filled with VPO-1 ion exchanger in the present invention; Fig.15 As shown in FIG. 1 , a VPO-1 sample preparation exchange column with a mass of about 1.15 g was filled into a 1 mL column. A constant flow pump was used to pump a pH of 6 and a sample containing Cs + , Sr 2+ The solution to be treated (the concentration of each ion was 2 ppm) was introduced into the exchange column and allowed to flow at a rate of 3 mL min -1 The flow rate flows through the exchange agent layer in the exchange column.
[0038] Example 6 The application of the ion exchanger in this embodiment is the same as that in Example 7, except that the pH value of the solution to be treated is 3, and the Cs + , Sr 2+ The annual concentration of ions is 0.5 ppm, and the -1 The flow rate flows through the exchange agent layer in the exchange column.
[0039] Example 7 The application of ion exchanger in this embodiment is the same as that in Example 7, except that the pH value of the solution to be treated is 12, and the Cs + , Sr 2+ The annual concentration of ions is 3000ppm, and the -1 The flow rate flows through the exchange agent layer in the exchange column.
[0040] Example 8 An application of an ion exchanger, specifically: First, the ion exchanger (VPO-1) prepared in Example 1 was made into a powder with a particle size of 5 μm, and then added into an N-methylpyrrolidone solution containing polyvinylidene fluoride to form a mixed solution, wherein the mass ratio of the ion exchanger to the polyvinylidene fluoride was 23:1.
[0041] Then the mixed solution was scraped onto the surface of the aqueous PTFE microporous filter membrane substrate and dried naturally in the air to obtain a VPO-1 / PTFE composite microporous filter membrane composed of an ion exchanger and PTEF; finally, the Cs + and Sr 2+ The solution to be treated flows through the microporous filter membrane, and the Cs + and Sr 2+ adsorption; wherein the thickness of the aqueous PTFE microporous filter membrane substrate is 118 µm; the thickness of the ion exchanger layer in the composite microporous filter membrane is 93 µm; the Cs + and Sr 2+ The ion concentration of each solution was 2 ppm and the pH value of the solution to be treated was 6.
[0042] Example 9 The application of the ion exchanger in this embodiment is the same as that in embodiment 10, except that: the mass ratio of the ion exchanger (VPO-1) to polyvinylidene fluoride is 5:1, the thickness of the aqueous PTFE microporous filter base is 30 µm; the layer thickness of the ion exchanger in the composite microporous filter is 200 µm; the Cs in the solution to be treated is 0.1. + and Sr 2+ The ion concentration of each solution was 0.5 ppm and the pH value of the solution to be treated was 12.
[0043] Example 10 The application of the ion exchanger in this embodiment is the same as that in embodiment 10, except that: the ion exchanger (VPO-1) is made into a powder with a particle size of 10 μm, the mass ratio of the ion exchanger to polyvinylidene fluoride is 40:1, the thickness of the aqueous PTFE microporous filter membrane substrate is 200 μm; the layer thickness of the ion exchanger in the composite microporous filter membrane is 10 μm; the Cs in the solution to be treated + The ion concentration is 0.5 ppm, Sr 2+ The ion concentration is 3000 ppm; the pH value of the solution to be treated is 3.
[0044] Test analysis 1. The calculation formula involved in the following test in the present invention is as follows: 1. Removal rate R (%) The removal rate R (%) of the present invention is calculated by the following method: (1); 2. Distribution coefficient K d (mL g -1 ) The distribution coefficient K of the present invention d (mL g -1 ) is calculated as follows: (2); 3. Pseudo-quadratic dynamics The pseudo-quadratic kinetic model of the present invention is expressed as: (3); 4. Langmuir isotherm adsorption model The Langmuir isotherm adsorption model of the present invention is expressed as: (4); 5. Frendlich isotherm adsorption model The Frendlich isotherm adsorption model of the present invention is expressed as: (5); In the above formulas (1) and (2), C0 (ppm) and C f (ppm) represent Cs in the solution + , Sr 2+ where V (mL) is the volume of the test solution and m (g) is the mass of the ion exchanger.
[0045] In formula (3), t (min) is the adsorption time, q t (mg g -1 ) and q e(mg g -1 ) represent Cs + , Sr 2+ The adsorption amount and equilibrium adsorption amount of ions at time t; k2 (g mg -1 min -1 ) is the pseudo-quadratic rate constant.
[0046] In formulas (4) and (5), q e (mg g -1 ) and q m (mg g -1 ) represent Cs + , Sr 2+ The equilibrium adsorption capacity and maximum adsorption capacity of ions; C e (ppm) is the adsorption equilibrium of Cs + , Sr 2+ Ion concentration; b (L mg -1 ) is the Langmuir constant, n and K are parameters that characterize the degree of heterogeneity of the system.
[0047] 2. Ion exchanger structure test 1. The morphology of the ion exchanger (VPO-1) prepared in Example 1 was observed using an optical microscope. The results are as follows: Figure 1 As shown; among them, Figure 1 The morphology of the ion exchanger (VPO-1) prepared in Example 1 of the present invention, (a) is the appearance morphology of VPO-1, and (b) is the enlarged appearance morphology of VPO-1. Figure 1 As can be seen from Figures (a) and (b) in FIG. 1 , the VPO-1 ion exchanger prepared in the present invention is in granular form.
[0048] 2. Figure 2 Schematic diagram of the crystal structure of the ion exchanger (VPO-1) prepared in Example 1 of the present invention, wherein (a) is {NaP4V 10 O 34}cluster composition diagram; (b) The figure shows [NaP4V 10 O 34 ] n 5n (c) The topology of the ion exchanger (VPO-1) framework; (d) The topology of the 18 {NaV 10 O 26}Schematic diagram of the nanoscale cavity encapsulated by clusters.
[0049] from Figure 2 As can be seen from the figure, the ion exchanger of the present invention has a crystal structure in which five [VO5] tetrahedral pyramids share edges and are connected to form a {V5O 17} unit; two {V5O 17} units are assembled together in a dimerized manner to form a {V 10 O 26} unit, and there is also a Na atom in the cavity; among them, {V5O 17 The oxygen atom at the junction of the units is shared with four phosphate groups to form {NaP4V 10 O 34} cluster (as shown in Figure a). {NaP4V 10 O 34 The clusters extend infinitely around each other by sharing the oxygen atoms on the phosphate groups, eventually forming a three-dimensional anion framework. + Ions occupy the pores and together form the crystal structure of VPO-1. These hydrated Na + Can be used with Cs + , Sr 2+ Perform ion exchange.
[0050] And, from Figure 2 It can be seen that the molecular formula of the ion exchanger (VPO-1) prepared in the present invention is Na6P4V 10 O 34 ·19H2O.
[0051] 3. The ion exchanger (VPO-1) prepared in Example 1 was analyzed using a scanning electron microscope. The test results are as follows: Figure 3 As shown, Figure 3 This is the energy dispersive X-ray spectrum of the ion exchanger (VPO-1) prepared in Example 1 of the present invention. Figure 3 It can be seen that the mass and atomic percentage of each element in the VPO-1 ion exchanger prepared by the preparation method of the present invention are consistent with the above-mentioned ion exchanger molecular formula Na6P4V 10 O 34 ·19H2O, the molecular formula of the ion exchanger prepared in Example 1 of the present invention can be further determined to be Na6P4V 10 O 34 ·19H2O.
[0052] 4. The ion exchanger (VPO-1) prepared in Example 1 was subjected to thermal analysis test under the following test conditions: argon gas, heating rate of 10 °C min -1 , the test results are as follows Figure 4 shown.
[0053] Figure 4 The thermogravimetric diagram of the ion exchanger (VPO-1) prepared in Example 1 of the present invention is shown in FIG. Figure 4It can be seen that the weight loss of VPO-1 ion exchanger in the temperature range of 40-250°C is 20.54%, which is basically consistent with the theoretical weight loss of 20.63% of the crystal water molecules in the material, further confirming that the VPO-1 molecular formula does contain 19 crystal water molecules, namely Na + Exists in the form of hydrated ions.
[0054] 5. The ion exchanger (VPO-1) prepared in Example 1 and its reaction with Cs + , Sr 2+ The saturated exchange products VPO-1Cs and VPO-1Sr were subjected to XRD analysis, and the test results are as follows Figure 5 shown.
[0055] Figure 5 The ion exchanger (VPO-1) prepared in Example 1 of the present invention and its reaction with Cs + , Sr 2+ XRD patterns of saturated exchange products VPO-1Cs and VPO-1Sr. Figure 5 It can be seen that the XRD pattern of VPO-1 prepared in the present invention is consistent with the spectrum fitted by single crystal data, proving that the phase purity of VPO-1 prepared by the method adopted in the present invention is high. + , Sr 2+ The peaks of VPO-1Cs and VPO-1Sr after ion exchange saturation and the spectrum of VPO-1 Figure 1 This indicates that the Na + In with Cs + , Sr 2+ After ion exchange, the crystal framework of the ion exchanger remains stable.
[0056] 6. The ion exchanger (VPO-1) prepared in Example 1 was irradiated with 50 kGy β or 150 kGy γ rays, and the VPO-1 before and after irradiation was analyzed by XRD. The test results are as follows: Figure 6 shown.
[0057] Figure 6 The XRD diagram of the ion exchanger (VPO-1) prepared in Example 1 of the present invention before and after 150 kGy β or 150 kGy γ ray irradiation. Figure 6 It can be seen that after the VPO-1 ion exchanger has been subjected to 150 kGyβ or 150 kGyγ high-intensity irradiation, its powder XRD spectrum is highly consistent with that before irradiation, which fully demonstrates that the material has not decomposed and the internal framework structure remains good; that is, it shows that the ion exchanger prepared by the present invention has excellent radiation resistance.
[0058] 3. Ion exchanger performance test analysis 1. Testing the performance of the ion exchanger after mixing it directly with the solution to be treated 1. Ion exchanger (VPO-1) for Cs + and Sr 2+ The adsorption dynamics of the supernatant in Example 4 was tested by diluting the supernatant by 250 times and then using ICP-MS (inductively coupled plasma mass spectrometry) to determine the Cs + , Sr 2+ The concentration of ions, the test results are as follows Figure 7 shown.
[0059] Figure 7 The ion exchanger (VPO-1) prepared in Example 1 of the present invention is used for Cs + or Sr 2+ The change of ion removal rate over time, where (a) is the VPO-1 sample for Cs + The removal rate of ions changes with time. (b) The VPO-1 sample is Sr 2+ The removal rate of ions changes with time. Figure 7 As can be seen from Figure (a), VPO-1 has a strong affinity for Cs + The exchange of Sr can reach equilibrium after 10 minutes, and it can be seen from Figure (b) that VPO-1 2+ The exchange equilibrium is after 20 minutes, and after equilibrium, Cs + , Sr 2+ The removal rates were all above 99.0%.
[0060] And compared with the first-order model, the pseudo-second-order kinetic model can better fit Cs + , Sr 2+ The kinetic data of VPO-1 and Cs + , Sr 2+ In the adsorption process, chemical adsorption is the rate-determining step. Figure 7 It can also be seen that VPO-1 has an effect on Cs + , Sr 2+ The exchange rate constants k2 are 3.774 g mg - 1 min -1 and 1.376 g mg -1 min-1 2. Ion exchanger for Cs + , Sr 2+ The isothermal adsorption of ions was tested as follows: sample VPO-1 was mixed with a single Cs +Solution to be treated (Cs in the solution to be treated + Ion concentration between 2-778 ppm (select 2, 5, 16, 21, 32, 46, 65, 92, 137, 166, 225, 274, 340, 460, 547, 778 ppm) or containing a single Sr 2+ The solution to be treated (Sr in the solution to be treated) 2+ The ion concentration was selected between 7-691 ppm (7, 15, 30, 65, 92, 194, 284, 386, 466, 582, 690 ppm) and then stirred for 1 hour at room temperature (20°C). The initial solution and the supernatant after the reaction were taken separately, and after being diluted 2500 times, the Cs + , Sr 2+ The concentration of ions; the relationship between the solution to be treated and the ion exchanger is V / m = 1000 mL g -1 , the pH of the solution to be treated is 6. The test results are as follows Figure 8 shown.
[0061] Figure 8 The ion exchanger (VPO-1) prepared in Example 1 of the present invention is used for Cs + or Sr 2+ Ion isotherm adsorption curve and fitting result diagram, among which (a) is the VPO-1 ion exchanger for Cs + Ion adsorption isotherm curve and fitting results. (b) Figure 2 shows the adsorption of Sr by VPO-1 ion exchanger. 2+ Ion adsorption isotherm curve and fitting results. Figure 8 It can be seen that VPO-1 has a strong effect on Cs + or Sr 2+ The adsorption capacity of the adsorbent increases with the increase of ion equilibrium concentration within a certain range. Figure 8 It can be further seen that VPO-1 has an effect on Cs + , Sr 2+ The maximum switching capacity q m The values were 300.32±7.69 mg g -1 and 113.00±5.76g·mgg -1 .
[0062] Then the above VPO-1 and Cs + , Sr 2+ The ion exchange products VPO-1Cs and VPO-1Sr were subjected to energy dispersive X-ray spectroscopy analysis, and the test results are as follows Fig. 9 and Fig.10 As shown, Fig. 9The ion exchanger (VPO-1) prepared in Example 1 of the present invention and Cs + Energy dispersive X-ray spectra of the ion exchange product VPO-1Cs; Fig.10 The ion exchanger (VPO-1) prepared in Example 1 of the present invention and Sr 2+ Energy dispersive X-ray spectrum of the saturation exchange product VPO-1Sr.
[0063] Combination Fig. 9 and Fig.10 It can be seen that VPO-1 and Cs + , Sr 2+ The mass percentage and atomic percentage of each element in the ion exchange products VPO-1Cs and VPO-1Sr are consistent with the elemental composition of VPO-1 after exchange and the Cs isothermal adsorption curve fitting. + , Sr 2+ Saturated adsorption capacity.
[0064] 3. Ion exchanger (VPO-1) at different pH values for Cs + , Sr 2+ The adsorption performance of ions was tested as follows: samples VPO-1 and samples with different pH values between 3 and 12 and containing Cs + and Sr 2+ ions (each ion concentration is 6 ppm) and the solution to be treated is mixed, and then stirred continuously at room temperature (20°C) for 1 hour. The relationship between the solution to be treated and the ion exchanger is V / m = 1000 mL g -1 Finally, the supernatant of the initial solution to be treated and the supernatant of the solution to be treated after the reaction were taken and diluted 250 times and then the Cs + , Sr 2+ The concentration of ions, the test results are as follows Fig.11 shown.
[0065] Fig.11 The ion exchanger (VPO-1) prepared in Example 1 of the present invention contains a single Cs + or Sr 2+ The distribution coefficient of ion adsorption varies with the pH value of the solution. (a) shows the distribution coefficient of ion adsorption of VPO-1 in the treated solution containing a single Cs + The distribution coefficient of ion adsorption varies with the pH value of the solution. (b) The figure shows the distribution coefficient of ion adsorption of VPO-1 in the treated solution containing a single Sr 2+ Distribution coefficient of ion adsorption versus solution pH.
[0066] from Fig.11It can be seen that VPO-1 exhibits good Cs in the pH range of 3-12. + and Sr 2+ Ion exchange activity, with significant acid and alkali resistance. When pH = 3-12, VPO-1 adsorbs Cs + , Sr 2+ Ion distribution coefficient K d Both are 2.22×10 4 mL·g -1 -2.17×10 5 mL g -1 In the range of pH=4-11, the removal rate is maintained between 95.68% and 99.54%. + Ion distribution coefficient K d Both reached 2.17×10 5 mL·g -1 Above (R Cs >99.20%). When pH=5-11, VPO-1 adsorbs Sr 2+ Ion distribution coefficient K d Both reached 2.78×10 5 mL·g -1 Above (R Sr >99.18%).
[0067] 4. The ion exchanger (VPO-1) contains Na + , K + ,Mg 2+ , Ca 2+ , CO3 2- , HCO3 - , NO3 - , SO4 2- , Al 3+ , Fe 3+ ,Eu 3+ , or UO2 2+ For single Cs + , Sr 2+ The adsorption performance test of ions is as follows: take samples VPO-1 and a single Cs + or Sr 2+ ions (each ion concentration is 6 ppm) and the solution to be treated was mixed, and then stirred at room temperature (20°C) for 1 hour. + , K + ,Mg 2+ , Ca 2+ (Each ion concentration is 0-100 mmol L -1 ), CO32- , HCO3 - , NO3 - , SO4 2- , Al 3+ , Fe 3+ ,Eu 3+ , or UO2 2+ (Each ion concentration is 30 ppm) High-valent ions, the relationship between the solution to be treated and the ion exchanger is V / m = 1000 mL g -1 , the pH of the solution to be treated is 6. Finally, the supernatant of the initial solution to be treated and the supernatant of the solution to be treated after the reaction were taken, diluted 250 times, and then the Cs + , Sr 2+ The concentration of ions, the test results are as follows Fig.12 , Fig.13 and Fig.14 shown.
[0068] Fig.12 The VPO-1 ion exchanger of the present invention is used for single Cs + , Sr 2+ Ion adsorption removal rate changes with the type and concentration of coexisting ions in the solution to be treated, where (a) is the removal rate of Cs by VPO-1 ion exchanger. + The removal rate of ion adsorption varies with the type and concentration of coexisting ions in the solution to be treated. (b) The removal rate of ion adsorption by VPO-1 ion exchanger is Sr 2+ The removal rate of ion adsorption varies with the type and concentration of coexisting ions in the solution to be treated.
[0069] from Fig.12 It can be seen that with VPO-1 as the exchange agent, R Cs and R Sr The changes with increasing concentrations of these ions (0-100 mmol L -1 At low concentrations (0.1-1 mmol L -1 ) down, Na + , K + Mg 2+ and Ca 2+ Cs + and Sr 2+ The interference of capture was minimal, and the removal efficiency was maintained between 93.30% and 99.55%. -1 Under these conditions, Na + , K + Mg 2+ It only has a small effect, so R Cs and RSr Remaining above 92.60% and 95.66% respectively.
[0070] Fig.13 The VPO-1 ion exchanger contains CO3 in the solution to be treated. 2- 、HCO3 - 、NO3 - or SO4 2- When present, single Cs + , Sr 2+ (6 ppm) removal rate by ion adsorption. Fig.13 It can be seen that in CO3 2- , HCO3 - , NO3 - , SO4 2- At concentrations of these ions around 30 ppm, VPO-1 still performs well as a Cs + The removal performance, R Cs The range is between 89% and 94%. - When the ion concentration is about 30ppm, Sr 2+ The adsorption was affected to a certain extent.
[0071] Fig.14 The VPO-1 ion exchanger contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ When present, single Cs + , Sr 2+ (6 ppm) removal rate by ion adsorption. Fig.14 It can be seen that Fig.14 As shown, in Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ When the concentration is 30 ppm, the presence of the above ions has an effect on the adsorption of Cs + and Sr 2+ The impact is very small, R Cs and R Sr All can be maintained above 88%.
[0072] (ii) Testing the performance of the ion exchanger after loading it into the chromatography column 1. According to the application in Example 5, the liquid flowing out of the exchange column was intercepted at intervals (0.5, 1, 2, 5, 10, 20, 40, and 60 minutes respectively), and the Cs content was determined by ICP-MS after being diluted 250 times. + , Sr 2+The concentration of ions was measured and the removal rate of the ion exchanger in 3000 mL of the solution to be treated was tested. The results are as follows Fig.16 shown.
[0073] Fig.16 The chromatographic column filled with the VPO-1 ion exchanger of the present invention is used to analyze the Cs + , Sr 2+ Ion removal rate versus bed volume. Fig.16 It can be seen that the ion exchange column filled with VPO-1 has a good performance on the removal of Cs in 3000 mL (3000 bed volumes) of pH=6 solution. + , Sr 2+ Ions can be efficiently adsorbed, Cs + and Sr 2+ The removal rate always remains above 99.5% and 98%.
[0074] 2. Ion exchanger adsorption of Cs + , Sr 2+ The elution and regeneration of the ion exchanger of ions were tested. The test was as follows: the saturated adsorption material VPO-1Cs (VPO-1 adsorbed Cs + to saturation) and VPO-1Sr (VPO-1 adsorbs Sr 2+ to saturation) with high concentration of Na + (2.0 M NaCl) aqueous solution was used to study the elution performance of VPO-1 ion exchanger. The test results are shown in Fig.17 , Fig.18 and Fig.19 As shown, Fig.17 Cs + and Sr 2+ SEM photos and element distribution diagrams of the saturated exchange products VPO-1Cs-Na and VPO-1Sr-Na after elution. Fig.18 Cs + This is the energy dispersive X-ray spectrum of the product VPO-1Cs-Na after elution of the saturated exchange product. Fig.19 Sr 2+ This is the energy dispersive X-ray spectrum of the product VPO-1Sr-Na after elution of the saturated exchange product.
[0075] Combination Fig.17 , Fig.18 and Fig.19 It can be seen that the morphology of the eluted material VPO-1 is well maintained, and EDS energy spectrum analysis detects Cs + , Sr 2+ The retention of ions is small, proving that the Cs + , Sr 2+Most of the ions are Na + Replace so that the material can be recycled.
[0076] (III) Performance test of ion exchanger after it is made into composite microporous membrane 1. The VPO-1 / PTFE composite microporous membrane prepared in Example 8 was analyzed by SEM. The test results are as follows: Fig. 20 shown.
[0077] Fig. 20 The SEM image of the cross section of the VPO-1 / PTFE composite microporous filter membrane of the present invention. Fig. 20 It can be seen that the VPO-1 particles in the VPO-1 / PTFE composite microporous membrane have a particle size of 20-40 μm, and the thickness of the exchange layer formed is about 130 μm. Compared with bulk materials, this design increases the specific surface area, thereby improving the adsorption rate.
[0078] 2. Test on the removal rate of VPO-1 / PTFE composite microporous membrane as the volume of treated solution changes The test is as follows: This test is the same as the application in Example 8, except that the volume of the solution to be treated by the composite microporous membrane is as high as 9000 mL, and the composite microporous membrane cycles three rounds of "adsorption-desorption" (i.e., adsorption and elution of the ion exchanger) during the treatment process. In the first round of adsorption, 5000 mL of Cs + and Sr 2 + The mixed solution (with a concentration of 2 ppm) was stirred at a rate of 1.19 mL min -1 cm -2 A constant flow rate of 1000 mL of 2M NaCl solution was passed through the membrane at the same rate to complete the first round of elution. Afterwards, the reusability of the membrane was evaluated by two additional cycles of adsorption (500 mL) and elution (1000 mL) under the same conditions.
[0079] (1) Observe the changes of the composite microporous filter membrane when treating the solution during the above test process. The results are as follows: Fig.21 shown.
[0080] Fig.21 The photo of the VPO-1 / PTFE composite microporous filter membrane during the test process of the present invention is shown in FIG. Fig.21 It can be seen that although the composite microporous filter membrane treated a volume of up to 9000 mL of the solution to be treated and three rounds of "adsorption-desorption" were carried out during the treatment process, the composite microporous filter membrane did not show obvious wrinkles or damage, that is, the prepared composite microporous filter membrane has good durability.
[0081] (2) According to the above test, the composite microporous filter membrane was observed to be mixed with Cs + , Sr 2+ The removal rate of ions (2 ppm for each ion) varies with the volume of the treated solution. The results are as follows: Fig. 22 shown.
[0082] Fig. 22 The VPO-1 / PTFE composite microporous filter membrane of the present invention is used to filter the mixed Cs + , Sr 2+ Ion removal rate versus treatment solution volume. Fig. 22 It can be seen that within the duration of 1600 mL, Cs + and Sr 2+ All of them were effectively removed, with removal rates reaching extremely high levels of 98.1%-99.5% and 97.1%-99.8%, respectively. This shows that VPO-1 has a strong affinity for these cations even at an ultra-short solution contact time of 0.65 seconds, which is consistent with the excellent kinetic properties of this material observed in batch tests. Cs and R Sr They steadily decreased over the next 3400 mL, reaching -1.6% and 13.6% respectively by the end of the experiment. Cs and R Sr The parallel decreasing slopes of indicate that VPO-1 binds to these two cations with comparable affinity. This property is of great significance for the simultaneous removal of 137 Cs and 90 Radionuclides such as Sr are particularly advantageous because they prevent competitive displacement between adsorbed species during kinetically driven membrane filtration. + and Sr 2+ The concentration ratio relative to the initial input (C t / C0) is expressed as a negative removal rate (R<0), which is the opposite of the adsorption process. Fig. 22 As shown, Cs + and Sr 2+ Rapid desorption, showing an unusually high negative removal rate (R Cs =−2156.32%; R Sr =−1395.91%). The desorption amount dropped sharply and decreased by 10 times in the next 100 mL (R Cs =−192.07%; R Sr=−135.09%) and then stabilized at approximately (−6 ± 2)% until the end of the 1000 mL treatment. The rapid elution process highlights the excellent reusability of the membrane, with continued high efficiency of Cs in the second and third adsorption cycles. + and Sr 2+ Remove.
[0083] The several embodiments described above are not intended to limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, shall be equivalent to making slight changes or modifications using the above technical contents.
Claims
1. A method for preparing an ion exchanger, characterized in that: The ion exchanger is prepared by dissolving V2O5, Na2HPO4·10H2O and an alkaline substance in distilled water to form a reaction solution, adding an acidic substance to the reaction solution to adjust the reaction solution to be weakly acidic, and then performing a hydrothermal reaction to obtain the ion exchanger.
2. The preparation method according to claim 1, characterized in that: The molar ratio of V2O5 to Na2HPO4·10H2O is 1:0.5-0.8; The pH value of the reaction solution after adjustment by the acidic substance is 3.8-4; The hydrothermal reaction conditions are: temperature 180-200°C, time 72-96h; The alkaline substance is diethylamine or pyridine; the acidic substance is acetic acid.
3. The ion exchanger prepared by the preparation method according to claim 1 or 2, characterized in that: The general structural formula of the ion exchanger is Na 5n [NaP4V 10 O 34 ] n · x H2O, where n >0, x is the number of free water molecules; the ion exchanger is [NaP4V 10 O 34 ] 5- Cluster formation, the [NaP4V 10 O 34 ] 5- The clusters are connected by oxygen atoms on the phosphate groups and extend infinitely around to form a three-dimensional anion framework, with the remaining sodium ions located within the framework.
4. The ion exchanger according to claim 3, characterized in that The [NaP4V 10 O 34 ] 5- The cluster is formed by two V5O7 units and four phosphate groups encapsulating one Na ion.
5. An application of an ion exchanger, characterized in that: The ion exchanger prepared by the preparation method of claim 1 or 2 or the ion exchanger of claim 3 or 4 is directly added to the Cs + and / or Sr 2+ In the solution to be treated, Cs + and / or Sr 2+ Adsorption; The pH value of the solution to be treated is 3-12; 1 g of ion exchanger is added to every 50-3000 mL of the solution to be treated; The solution to be treated contains Cs + The concentration of ions is 0.1-3000ppm; Sr 2+ The concentration of ions is 0.1-3000ppm.
6. The use according to claim 5, characterized in that: The solution to be treated also contains Na + , K + Mg 2+ and Ca 2 + At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm.
7. An application of an ion exchanger, characterized in that: The ion exchanger prepared by the preparation method of claim 1 or 2 or the ion exchanger of claim 3 or 4 is filled in a chromatography column, and the ion exchanger containing Cs + and / or Sr 2+ The solution to be treated flows through, and the Cs + and / or Sr 2+ Adsorption; The solution to be treated contains Cs + and Sr 2+ The concentration of ions is 0.5-3000 ppm; Every 1 cm 3 The flow rate of the ion exchanger to treat the solution to be treated is 0.1-5 mL min -1 ; The pH value of the solution to be treated is 3-12.
8. The use according to claim 7, characterized in that: The solution to be treated also contains Na + , K + Mg 2+ and Ca 2 + At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm.
9. An application of an ion exchanger, characterized in that: First, the ion exchanger prepared by the preparation method of claim 1 or 2 or the ion exchanger of claim 3 or 4 is made into powder and added into N-methylpyrrolidone dissolved with polyvinylidene fluoride to form a mixture, then the mixture is taken out and evenly scraped on the surface of the aqueous PTFE microporous filter membrane substrate, and naturally dried in the air to obtain a composite microporous filter membrane composed of the ion exchanger and PTFE; by suction filtration, the Cs + and / or Sr 2+ The solution to be treated flows through the composite microporous filter membrane, and the Cs + and / or Sr 2+ Adsorption; The mass ratio of the ion exchanger to polyvinylidene fluoride is 5-40:1; The thickness of the aqueous PTFE microporous filter membrane substrate is 30-200 μm; The layer thickness of the ion exchanger in the composite microporous filter membrane is 10-200 μm; Every 1 cm 2 The flow rate of the composite microporous filter to treat the solution to be treated is 0.5-2.5 mL min -1 ; The solution to be treated contains Cs + and Sr 2+ The concentration of the ions is 0.5-3000 ppm; the pH value of the solution to be treated is 3-12.
10. The use according to claim 9, characterized in that: The particle size of the powder made of the ion exchanger is 1-10 μm; The solution to be treated also contains Na + , K + Mg 2+ and Ca 2+ At least one of the ions has a concentration of 0-1000 mmol L -1 ; The solution to be treated also contains Fe 3+ 、Al 3+ 、Eu 3+ and UO2 2+ The concentration of at least one of the ions is 0-100 ppm.
Citation Information
Patent Citations
Cs < + > and Sr < 2 + > co-adsorption-separation difunctional ion exchanger as well as preparation method and application thereof
CN114669269A
Novel metal ion-exchanged phosphorus-vanadium compound and solid acid catalyst using compound
CN1173396A
High-selectivity Cs < + > ion exchanger as well as preparation method and application thereof
CN118454754A
Novel metal ion-exchanged phosphorusvanadium compound and solid acid catalyst using the compound
EP0794151A1